Role of Environmental Law and International Conventions in Mitigating Climate Change Effects on Food System and Livestock Production - Chowdhury, Amtul; Hossain, Mohammad Belayet (Lex Publica, 2021)
Climate change nowadays is a global threat that is driven by human-induced greenhouse gas emissions and the changeable pattern of global weather. Though there have been previous periods of climatic change since the mid-20th century, humans have had an unprecedented impact on earth’s climate system and caused change on a global scale. Consequently, this is affecting the whole food system throughout the world. The utilization of the international legal framework and protocols will have an impact on the human’s food system and livestock production. This paper intends to focus on using legal frameworks and protocols to erase the impact of climate change on the food system and livestock production. By using the quantitative research method due to the pandemic situation, this study will explain the broad uses of the Kyoto protocol and Polluter Pays Principle and shall discuss various methods that will help these principles to erase the negative impact of climate change globally. Based on the findings, this paper provides recommendations that could be considered by the developed country to use the legal and social protocols for improving the impact of climate change on the food chain system of humans and livestock production. Abstrak Perubahan iklim saat ini merupakan ancaman global yang didorong oleh emisi gas rumah kaca yang disebabkan oleh manusia dan perubahan pola cuaca global. Meskipun telah terjadi periode perubahan iklim sebelumnya, sejak pertengahan abad ke-20 manusia telah memberikan dampak yang belum pernah terjadi sebelumnya pada sistem iklim Bumi dan menyebabkan perubahan dalam skala global. Akibatnya, ini mempengaruhi seluruh sistem pangan di seluruh dunia. Pemanfaatan kerangka hukum dan protokol internasional akan berdampak pada sistem pangan manusia dan produksi ternak. Makalah ini bermaksud untuk fokus pada pemanfaatan kerangka hukum dan protokol untuk menghapus dampak perubahan iklim terhadap sistem pangan dan produksi ternak. Dengan menggunakan metode penelitian kuantitatif karena situasi pandemi, penelitian ini akan menjelaskan penggunaan yang lebih luas dari protokol Kyoto, Polluter Pays Principle dan akan membahas berbagai metode yang akan membantu prinsip-prinsip ini untuk menghapus dampak negatif perubahan iklim secara global. Berdasarkan temuan makalah ini memberikan rekomendasi yang dapat dipertimbangkan oleh negara maju untuk menggunakan protokol hukum dan sosial untuk meningkatkan dampak perubahan iklim sistem rantai makanan manusia dan produksi ternak. Kata kunci: Perubahan iklim, Emisi rumah kaca, Produksi ternak, Protokol Kyoto, Prinsip pencemar membayar